The Students Ability to Use Verbs in Completing Recount Text - Sene, Chamelya Vivi Crystanty; Lodo, Rozita Yusniaty; Tefa, Antonia; Mola, Mansuetus; Manek, Agnes O. (INTERACTION: Jurnal Pendidikan Bahasa, 2024)
The objectives of this study are to assess the proficiency of second-grade students in utilizing suitable verbs to complete a recount text and to identify the challenges encountered by these students in completing a recount text at the junior high school level. The researcher employed a qualitative approach to analyze the data. The study included a population of 20 students, and the researcher selected a random sample of 15 students. The researcher used a test as a tool to complete the recount text, selecting appropriate verbs from the provided list. The researcher employed various formulas to analyze the data. The findings indicate that the second-grade students lack proficiency in selecting suitable verbs to effectively complete the text. The analysis supports this conclusion, revealing a competency level of 56.52% among the students. We classify this skill as "poor," and the pupils achieved an average grade of 56.33%.